2023
DOI: 10.6018/analesps.499371
|View full text |Cite
|
Sign up to set email alerts
|

What do we know about highly effective therapists? A systematic review

Abstract: Highly effective therapists are clinicians who systematically achieve excellent therapeutic outcomes. However, variables that could explain this performance still unknown. To identify these variables (i.e., definition, objective measurements; and the degree to which the independent variables measure what it claims) could help to know more about highly effective therapists’ performance. Therefore, a systematic review was conducted. Publications between 2000 and 2020 -from Scopus, MEDLINE/PubMed, Web of Science,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…These differences in ability to form these relationships have been shown to impact clinical effectiveness (2). "Master" or expert therapists differ from novices, and even professional therapists, in several important ways (8,(25)(26)(27). A hallmark of these experts is the clinician's technical skill, as well as her response to larger contextual issues (7,8).…”
Section: Expert Psychotherapists Psychotherapy Over Time Video Series...mentioning
confidence: 99%
See 2 more Smart Citations
“…These differences in ability to form these relationships have been shown to impact clinical effectiveness (2). "Master" or expert therapists differ from novices, and even professional therapists, in several important ways (8,(25)(26)(27). A hallmark of these experts is the clinician's technical skill, as well as her response to larger contextual issues (7,8).…”
Section: Expert Psychotherapists Psychotherapy Over Time Video Series...mentioning
confidence: 99%
“…However, approximately 15–20% of clinicians could be identified with consistently good outcomes, and approximately the same level for clinicians with consistently poorer outcomes ( 11 ). More recently, Pereira et al ( 25 ) conducted a systemic review of highly effective therapists and found that emotional expression was a significant predictor of therapist effectiveness. It stands to reason that clinicians who consistently have better outcomes, must construct their therapeutic relationships differently than other professional clinicians.…”
Section: Expert Psychotherapists Psychotherapy Over Time ...mentioning
confidence: 99%
See 1 more Smart Citation